2000
DOI: 10.1007/s002440010079
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Size-Specific Mercury Concentrations in Game Fish from Maryland Fresh and Estuarine Waters

Abstract: Abstract.A survey of size-specific mercury (Hg) concentrations in game fish from a subset of Maryland fresh and estuarine waters was conducted, in which Hg concentrations in 112 fish from seven freshwater impoundments and three tidal and four estuarine locations in Chesapeake Bay and its tributaries were measured. Striped bass (Morone saxatilis) was the most intensively examined species. Of the fish examined, the largest freshwater sportfish contained the highest Hg concentrations. Striped bass and largemouth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
2
28
3
Order By: Relevance
“…The size of a fish is known as a determining factor of its Hg burden (Mackay et al, 1975;Jaffar and Ashraf, 1988;Bloom, 1992;Dietz et al, 1996;Gilmour and Riedel, 2000;Stafford and Haines, 2001;Kraepiel et al, 2003), and has been confirmed here.…”
Section: Mercury Size Sex Species and Locationsupporting
confidence: 76%
See 2 more Smart Citations
“…The size of a fish is known as a determining factor of its Hg burden (Mackay et al, 1975;Jaffar and Ashraf, 1988;Bloom, 1992;Dietz et al, 1996;Gilmour and Riedel, 2000;Stafford and Haines, 2001;Kraepiel et al, 2003), and has been confirmed here.…”
Section: Mercury Size Sex Species and Locationsupporting
confidence: 76%
“…In most fish, muscle Hg content increases with the size of the individual (Mackay et al, 1975;Monteiro and Lopes, 1990;Bloom, 1992;Dietz et al, 1996;Gilmour and Riedel, 2000;Stafford and Haines, 2001). The difference in the average length of fish is thus a bias when comparing subsamples using comparison tests such as those described above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hg growth enrichment and biomass dilution in fish One of the most interesting aspects regarding Hg in fish is 'growth enrichment'−the phenomenon that larger fish contain higher Hg (mostly MeHg) concentrations (e.g., Gilmour andRiedel 2000, Magalhaes et al 2007). Different from many other trace metals, mercury is generally accumulated in fish in proportion to its size (Joiris et al 2000, Wiener et al 1990, Peterson and Sickle 2007, Monterio and Lopes 1990, Sonesten 2003, Storelli et al 2007, Gewurtz et al 2011, Staudinger 2011, Qiu et al 2011.…”
Section: Significance Of Hg Speciation and Fish Physiology In Waterbomentioning
confidence: 99%
“…Therefore, while apparent Hg concentrations in specific fish tissue may vary over time, the relative influence of factors such as environmental fluctuations (pH, temperature, dissolved organic carbon, nutrient availability) and changes in fish physiology should be taken into account when results are interpreted (Mass-DEP, 2006). Concentrations of Hg can be influenced by fish size (Gilmour and Riedel, 2000), a factor that can easily vary among sampling periods. Hence, seasonal changes in the Hg concentrations in aquatic ecosystems have been investigated and documented in many studies aiming to describe seasonal patterns in freshwater food webs (Meili and Wills, 1985;Staveland et al, 1993;Slotton et al, 1995;Park and Curtis, 1997;Gorski et al, 1999;Farkas et al, 2003;Murphy et al, 2007;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%